2023
DOI: 10.30574/wjarr.2023.17.1.0088
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicine claim directed in-silico prediction of epidermal growth factor receptor kinase antagonist: an untapped reservoir of prospective anticancer agents

Abstract: The epidermal growth factor receptor (EGFR) is a tyrosine kinase (TK) that belongs to the ErbB family and governs important cellular functions like reproduction, survival, motility, and differentiation. Overexpression, intensification, and alteration of EGFR occur in a wide range of human malignancies and are associated with tumor progression and decreased anticancer drug sensitivity. As a result, EGFR has been identified as one of the primary anticancer targets. As cancer is more likely to be poorly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“… 83 In addition, other factors such as temperature, solvent conditions, and simulation parameters can also influence Rg values and protein stability. 78 These results provide insights into the structural dynamics of the protein targets in a complex with berberine and highlight the potential impact of ligand binding on protein stability and flexibility.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“… 83 In addition, other factors such as temperature, solvent conditions, and simulation parameters can also influence Rg values and protein stability. 78 These results provide insights into the structural dynamics of the protein targets in a complex with berberine and highlight the potential impact of ligand binding on protein stability and flexibility.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that the RMSD of a ligand can be affected by the conformational changes of the protein side chains that form hydrogen bonds or van der Waals interactions with the ligand. 78 , 79 Therefore, differences in the binding interactions of different protein target with berberine may also contribute to the differences in their RMSD values. In summary, the RMSD plot of the MD simulation provides valuable information about the stability and conformational changes of the protein-ligand complex.…”
Section: Discussionmentioning
confidence: 99%
“…To identify a potential medication that could inhibit the function of epidermal growth factor receptor kinase, protein-ligand docking studies were conducted using Autodock Vina and PyRx 8.0. [17] The grid map for docking calculations was centered on the target proteins, and BIOVIA Discovery Studio version 21.1 was utilized to simulate non-bonded polar and hydrophobic interactions at the inhibitor site of 3RKJ. Standard docking protocols were employed for subsequent docking procedures.…”
Section: Molecular Dockingmentioning
confidence: 99%